Absconding During Inpatient Care from a Tertiary Psychiatric Hospital: A Comparative Study - Verma, Dileep Kumar (Indian J Psychol Med, 2020)
BACKGROUND: Absconding from psychiatric hospitals is of great concern for patients and caregivers. Absconding affects not only the treatment and safety of these patients but also patient’s caregivers and the community. Further investigation is needed to examine the pattern of this event and the characteristics of patients who abscond. Hence, our study was aimed to examine the sociodemographic and clinical profiles of inpatients who absconded from a psychiatric hospital in five years and to compare them with matched controls. METHODS: A retrospective chart review of inpatients who absconded and matched control inpatients during the specified period of five years from January 2014 to December 2018 was done at a psychiatric hospital. Each control was matched with a corresponding absconding case on the following order: (a) admission ward, (b) admission period, (c) diagnosis, and (d) age. Results: Among 20,052 adult admissions during the specified period, 38 patients absconded, with a rate of 1.8 per 1,000 admissions. Most of them were male, from a younger age group, diagnosed with schizophrenia or mood disorder, and having comorbid substance use disorder, irritable affect, impaired judgment, and absent insight. Most of the events occurred within the first two weeks of admission. About 11% of them had a history of prior absconding from the hospital. CONCLUSION: Knowledge about the associated sociodemographic and clinical profile would help clinicians and mental health care professionals to prevent absconding. Further risk assessment using a patient’s profile would help to reduce absconding events from psychiatric hospitals in the future.